2021
DOI: 10.3390/s21206789
|View full text |Cite
|
Sign up to set email alerts
|

Dry Wearable Textile Electrodes for Portable Electrical Impedance Tomography

Abstract: Electrical impedance tomography (EIT), a noninvasive and radiation-free medical imaging technique, has been used for continuous real-time regional lung aeration. However, adhesive electrodes could cause discomfort and increase the risk of skin injury during prolonged measurement. Additionally, the conductive gel between the electrodes and skin could evaporate in long-term usage and deteriorate the signal quality. To address these issues, in this work, textile electrodes integrated with a clothing belt are prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…This result indicated that the purpose of early research on EIT hardware was to improve the EIT image quality [‘contrast’ and ‘distinguishability’ ( Adler et al, 2011 ) ] through the cooperation of hardware (‘electrode model’ ( Mueller et al, 1999 )) and algorithm (‘state estimation’ ( Kolehmainen et al, 2001 ) and ‘decomposition’ ( Clay and Ferree, 2002 )). Recent keywords mainly focus on the performance improvement of each module of EIT hardware system by applied new designs or techniques, including ‘voltage measurement’ ( Fu et al, 2022 ; Shi et al, 2022 ), current source (‘Howland current source’ ( Oh et al, 2011 ), ‘current driver’ ( Hong et al, 2010 ; Shahghasemi, 2020 )and ‘output impedance’ ( Shishvan et al, 2021 )) and novel electrode sensor (‘textile electrodes ( Katashev et al, 2018 ; Hu et al, 2021 )’ and ‘active electrode’ ( Wu et al, 2019 )). For example, Saulnier et al and Liu et al designed a DSP-based current source and a FPGA-based adaptive different current source in order to meet the requirement of high output impedance for current source in the most popular EIT hardware frameworks with a parallel and multiple source architecture ( Saulnier et al, 2020 ; Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This result indicated that the purpose of early research on EIT hardware was to improve the EIT image quality [‘contrast’ and ‘distinguishability’ ( Adler et al, 2011 ) ] through the cooperation of hardware (‘electrode model’ ( Mueller et al, 1999 )) and algorithm (‘state estimation’ ( Kolehmainen et al, 2001 ) and ‘decomposition’ ( Clay and Ferree, 2002 )). Recent keywords mainly focus on the performance improvement of each module of EIT hardware system by applied new designs or techniques, including ‘voltage measurement’ ( Fu et al, 2022 ; Shi et al, 2022 ), current source (‘Howland current source’ ( Oh et al, 2011 ), ‘current driver’ ( Hong et al, 2010 ; Shahghasemi, 2020 )and ‘output impedance’ ( Shishvan et al, 2021 )) and novel electrode sensor (‘textile electrodes ( Katashev et al, 2018 ; Hu et al, 2021 )’ and ‘active electrode’ ( Wu et al, 2019 )). For example, Saulnier et al and Liu et al designed a DSP-based current source and a FPGA-based adaptive different current source in order to meet the requirement of high output impedance for current source in the most popular EIT hardware frameworks with a parallel and multiple source architecture ( Saulnier et al, 2020 ; Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wearables are especially useful in monitoring chronic conditions such as COPD or heart failure; therefore, a long term, independent use in a non-controlled environment (such as the patient’s home) is envisioned. Ag/AgCl electrodes with conductive gel may be problematic for these applications: the preparation of the patient’s skin may be problematic in a non-controlled environment [ 46 ]; the conductive gel may cause discomfort, increasing the risk of skin injury for prolonged measurements and may evaporate, resulting in a deterioration of the signal quality [ 47 ]. So, dry electrodes (not requiring a conductive gel) are usually preferred for wearable devices [ 46 ], both rigid (made of a metallic plate) and flexible.…”
Section: Electrical Impedance Tomographymentioning
confidence: 99%
“… Application in medical. ( a ) Use FMG and machine learning techniques to differentiate between grasping and no grasping [ 169 ]; ( b ) textile electrodes integrated with a clothing belt for EIT lung imaging [ 170 ]; ( c ) assisted rehabilitation design of 3D printed hand exoskeleton based on FMG control [ 171 ]; ( d ) EMG biofeedback device for gait rehabilitation [ 172 ]; ( e ) detection of changes in lower extremity muscle impedance properties immediately after functional electrical stimulation-assisted cycling training in chronic stroke survivors [ 173 ]; ( f ) an evaluation of spontaneous respiratory idiopathic pulmonary fibrosis using EIT [ 174 ]. …”
Section: Figurementioning
confidence: 99%